1999
DOI: 10.2134/jeq1999.00472425002800010014x
|View full text |Cite
|
Sign up to set email alerts
|

Isoproturon Sorption and Degradation in a Soil from Grassed Buffer Strip

Abstract: The fate of the herbicide isoproturon [3‐(4‐isopropylphenyl)‐l,1‐dimethylurea] was investigated in soil from a grassed buffer strip. Compared to a cropped soil originating from the same experimental site (Kd = 1.8 L kg−1), sorption of isoproturon was enhanced in the grassed soil and especially in the surface layer (0‐2 cm) containing high proportion of nondecomposed plant residues (Kd = 5.0 L kg−1). Nonhumified organic fractions isolated from the surface soil layer and corresponding to above and bdow‐ground pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
84
0
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(93 citation statements)
references
References 0 publications
4
84
0
5
Order By: Relevance
“…The screening method using HPLC coupled with UV detection has been extensively used to monitor the degradation of pesticides in soils (Anderson and Dulka, 1985;Shneiders et al, 1993;Thapar et al, 1995;Benoit et al, 1999) EXPERIMENTAL PROCEDURE Chemicals and soils. Imazosulfuron (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The screening method using HPLC coupled with UV detection has been extensively used to monitor the degradation of pesticides in soils (Anderson and Dulka, 1985;Shneiders et al, 1993;Thapar et al, 1995;Benoit et al, 1999) EXPERIMENTAL PROCEDURE Chemicals and soils. Imazosulfuron (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Benoit et al (1999) reported high levels of sorption and rapid degradation of isoproturon in soil from a perrenial ryegrass (Lolium perenne) buffer strip. Mersie et al (1999a) used small boxes of soil and simulated runoff to assess the effect of switchgrass buffers, which increased herbicide retention over bare soil.…”
Section: Introductionmentioning
confidence: 99%
“…For pesticide inputs, field measurements of the percentage of clay (PTC) and organic carbon (PCTOC) of the upper field followed a uniform PDF (Lacas, 2005;Benoit et al, 1998;Madrigal-Monarrez, 2004). The triangular distribution for KOC for the pesticides evaluated at each site is based on measurements in Jaillière for the base value and boundaries (Benoit et al, 1998;Souiller et al, 2002) and on Morcille for the base value (Lacas, 2005) but using boundaries from the PPDB database (IUPAC, 2007).…”
Section: Selection Of Inputs and Outputs For Gsa Simulationsmentioning
confidence: 99%
“…The triangular distribution for KOC for the pesticides evaluated at each site is based on measurements in Jaillière for the base value and boundaries (Benoit et al, 1998;Souiller et al, 2002) and on Morcille for the base value (Lacas, 2005) but using boundaries from the PPDB database (IUPAC, 2007).…”
Section: Selection Of Inputs and Outputs For Gsa Simulationsmentioning
confidence: 99%